CONFRONTATION OF HUNTING SPIDERS (ARANEAE: ANYPHAENIDAE AND SALTICIDAE) WITH SPIDER MITES (ACARI: ERIOPHYIDAE E TENUIPALPIDAE) IN RUBBER TREE (Hevea brasiliensis) - Ferrari Filho, Paulo Eduardo Bedin; Rinaldi, Isabela Maria Piovesan; Feres, Reinaldo JosÃ© Fazzio (REVISTA DE AGRICULTURA, 2015)
CONFRONTATION OF HUNTING SPIDERS (ARANEAE: ANYPHAENIDAE AND SALTICIDAE) WITH SPIDER MITES (ACARI: ERIOPHYIDAE E TENUIPALPIDAE) IN RUBBER TREE (Hevea brasiliensis)